Stan Naprężenia i Przemieszczenia w Grubej Płycie Kołowej, Wywołany Działaniem Nieustalonego Pola Temperatury - Derski, W. (Engineering Transactions, 1961)
This is a continuation of the paper [7]. The solutions obtained in that paper are represented by sums of simple and double series, which are of slow convergence in the case of small times. However, in such cases of heating as are considered in the paper mentioned the first seconds of action of the heat source are of particular interest. With increasing time the stresses decrease and tend to the steady-state values. In the first seconds of the heating process the maximum stress should arise, in view of the temperature gradient, in outer strata.In the present paper asymptotic equations are given enabling, with practically sufficient accuracy, the description of the variability of stress in outer strata in the first seconds of the heating process. It should be added that all the mechanical conditions are the same as in the first part of the work.